Upaya Menurunkan Nyeri Dengan Mobilisasi Dini Pada Pasien Post Operasi Sectio Caesarea Dengan Spinal Anestesi - Happy Nurhayati; Galih Pria Pambayun; Clara febyola (Journal Pharma Saintika, 2021)
Background: Spinal anesthesia is a procedure performed by injecting a local anesthetic into the subarachnoid space. Sectio caesarea is a delivery process that does not pass through the birth canal but is an artificial process of expelling the fetus through abdominal surgery. The process of abdominal surgery causes wounds and has an impact on the mother, the most felt impact is acute pain. Early mobilization is one of the non-pharmacological approaches used to reduce postoperative pain.. Objective: Knowing the effect of early mobilization on postoperative cesarean section pain and acute pain nursing problems in the Bougenvil Room of RSUD dr. Sudirman, Kebumen.. Methods: The method in this case study uses data collection methods through interviews, observations, and documentation and is added using case study instruments which include: assessment, diagnosis, intervention, implementation, and evaluation carried out on 5 post Sectio Caesarea patients. So that the case study obtained a priority diagnosis of acute pain. The implementation carried out on both clients is to identify the location, characteristics, duration, frequency, quality and intensity of pain, provide a comfortable position for the patient, provide relaxation and distraction technique therapy: gradual mobilization, provide analgesic therapy according to doctor's advice. Early mobilization distraction techniques are joint motion exercises, gait, activity tolerance according to ability and body alignment. Evaluation of the five patients with acute pain nursing problems found that the patient said the pain was reduced.. Results: after the anesthetic nursing action the pain decreased slightly. Conclusion: performing non-pharmacological techniques (early mobilization) resulted in slightly reduced pain in post-sectional Caesarea patients